The craft of professional writing : a guide for amateur and professional writers - Malone, Michael S. (Michael Shawn), 1954- (London : Anthem Press, 2018)
The Craft of Professional Writing is the most complete book ever written about the real-life work of being a writer. Covering topics ranging from business writing (advertising, PR) to commercial work (news reporting, feature writing, blogging, non-fiction books) to creative writing (screenplays and novels), as well as advice on pitching, rejection and leading a writer's life, the narrative is filled with anecdotes and illuminating stories, as well as tricks of the trade in each form of writing. For the student, The Craft of Professional Writing is the most wide-ranging and practical textbook on the subject. Designed to be an instructional text for producing professional-level work, it is also a survey of the various writing professions to enable budding writers to make career decisions. For the professional, this book is the ultimate reference work offering practical tips and advice they can return to again and again to help them through various phases of their career.
Title from publisher's bibliographic system (viewed on 02 Aug 2018).
Keywords: Authorship -- Handbooks, manuals, etc; Authorship -- Vocational guidance -- Handbooks, manuals, etc